Correspondence on sitagliptin and cardiovascular outcomes in type 2 diabetes - Holman, R; Peterson, E (Massachusetts Medical Society, 2015)
The concerns raised by Rutter et al. with respect to possible unequal open-label drop-in of glucose-lowering agents were considered in the risk-assessment component of our trial design. Rosiglitazone was not permitted at enrollment in our trial, and its use was discouraged during the trial because of ongoing concerns about its cardiovascular safety profile. The protocol mandated the inclusion of a minimum of 2000 patients who were receiving pioglitazone. However, the protocol was amended because so few patients who were receiving that agent could be identified; only 396 of the 14,735 patients who underwent randomization (2.7%) were receiving pioglitazone. Baseline use of a thiazolidinedione did not have an effect on the risk of hospitalization for heart failure. Postbaseline use of thiazolidinediones increased marginally to 3.6% in the sitagliptin group and 4.2% in the placebo group.